Analisis Citra Merek, Kualitas Produk dan Kualitas Layanan Terhadap Kepuasan Konsumen (Survey Pengunjung Kopi Dari Hati Marisa) - Fauzia Rukmana Poha; Deby Rita Karundeng; Moh Afan Suyanto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Fauzia Rukmana Poha, 2021. "Brand Image Analysis, Product Quality, Service Quality on customer satisfaction (study on visitors to the Coffee Shop Kopi Dari Hati Marisa)". (Under the guidance of Deby Rita Karundeng as chairman of the supervisory committee and Moh. Afan Suyanto as a member of the supervisor). This study aims to determine the effect of "Brand Image Analysis, Product Quality and Service Quality on consumer satisfaction (study on visitors to Coffee Shop Kopi Dari Hati Marisa)". The data used in this study is primary data sourced from filling out questionnaires. The sample of this study amounted to 70 respondents. The analytical technique used to answer the research problem and test the hypothesis is multiple linear regression analysis. The data is processed using the StatisticalProdct Service Solution (SPSS) application. The results of this study are (1) There is a positive and significant effect of brand image on consumer satisfaction (study on visitors to the Coffee Shop Kopi Dari Hati Marisa)”, (2) There is a positive and significant effect of product quality on consumer satisfaction (study on visitors to Coffee Shop Coffee From the Heart of Marisa)", (3) There is a positive but not significant effect on the quality of service on consumer satisfaction (study on visitors to the Coffee Shop Kopi Dari Hati Marisa)".